2009
DOI: 10.1194/jlr.m800582-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine hydroperoxide-induced THP-1 cell adhesion to intracellular adhesion molecule-1

Abstract: The accumulation of phosphatidylcholine hydroperoxide (PCOOH), a primary oxidation product of phosphatidylcholine (PC), in blood plasma and tissues has been observed in various pathological conditions, including atherosclerosis. However, the biological roles of PCOOH in these conditions remain unknown. To estimate the atherogenicity of PCOOH, we evaluated the effect of PCOOH on THP-1 monocytic cell adherence to immobilized vascular endothelial cell adhesion molecules. THP-1 cell adhesion to intracellular adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…In another experiment, we found that PCOOH stimulated angiogenic responses in HUVECs (23). These previous findings (21)(22)(23) together with our recent results (24) will enhance our fundamental understanding of the involvement of PCOOH in Ox-LDL in the development of atherosclerosis, although further studies are needed to investigate atherogenic processes (e.g., cytotoxicity, apoptosis, mitotic catastrophe, ferroptosis, and angiogenesis) of PCOOH in Ox-LDL.…”
Section: Biological Roles Of Pcooh In Atherogenesissupporting
confidence: 71%
See 1 more Smart Citation
“…In another experiment, we found that PCOOH stimulated angiogenic responses in HUVECs (23). These previous findings (21)(22)(23) together with our recent results (24) will enhance our fundamental understanding of the involvement of PCOOH in Ox-LDL in the development of atherosclerosis, although further studies are needed to investigate atherogenic processes (e.g., cytotoxicity, apoptosis, mitotic catastrophe, ferroptosis, and angiogenesis) of PCOOH in Ox-LDL.…”
Section: Biological Roles Of Pcooh In Atherogenesissupporting
confidence: 71%
“…However, the biological mechanism has not been definitively established. We previously found that THP-1 cell adhesion to intracellular adhesion molecule-1 was increased in the presence of PCOOH (21,22). The result indicates that PCOOH in Ox-LDL may be involved in monocyte adherence to the arterial wall during the initiation of atherosclerosis.…”
Section: Biological Roles Of Pcooh In Atherogenesismentioning
confidence: 91%
“…Although the surface expression remained consistent in THP-1 monocytes, the conformation changed to the high-affinity conformation, which may explain the increase in adhesion of ␤-hydroxybutyrate-treated cells, since neither LFA-1 nor ICAM-1 surface expression was increased with ␤-hydroxybutyrate treatment. Previous studies in the literature have also reported that, when treated with phosphatidylcholine hydroperoxide, the expression of LFA-1 does not increase in THP-1 monocytes, but the activation state changes, resulting in increased adhesion to ICAM-1 (4). These data suggest that physiological concentrations of both acetoacetate and ␤-hydroxybutyrate may result in upregulation and activation of adhesion molecules as a way to recruit an increased number of monocytes to the vascular endothelium.…”
Section: E301 Hyperketonemia Induces Monocyte-endothelial Cell Adhesionmentioning
confidence: 54%
“…Reactive oxygen species (ROS) generation was measured using 5-(and-6)-carboxy-2Ј,7Ј-difluorodihydrofluorescein diacetate (carboxy-H 2 DFFDA; Invitrogen) as described previously. 30 In brief, cells were washed in PBS, treated with 5M 5-(and-6)-carboxy-2Ј,7Ј-difluorodihydrofluorescein diacetate for 30 minutes at 37°C, and washed twice with PBS. The resulting fluorescence was analyzed by flow cytometry.…”
Section: Sod2 Activity and Ros Measurementmentioning
confidence: 99%